EFFECT OF WORK SKILLS, WORK ENVIRONMENT AND LEADERSHIP STYLE ON EMPLOYEE PERFORMANCE (Study at LG Electronics Indonesia PT-Head Office in South Jakarta) - Juniarti, Septiani; Yennida Parmariza; NurulIzza Maharani (Dinasti International Journal of Digital Business Management, 2022)
This study aims to determine the effect of work skills, work environment & leadership style on employee performance at LG Electronics Indonesia PT-Head Office in South Jakarta. LG Electronics is a multinational company from South Korea. LG Electronics is the second largest South Korean company in the field of electronic devices and the third largest in the world in the field of manufacturing similar devices. With the existence of LG Electronics Indonesia PT. The Head Office in South Jakarta certainly needs to be developed to improve employee performance so as to assist the company in achieving the company's vision and mission. This research includes causal associative research using a quantitative approach. The sample in this study were 30 people in the study. The sample technique used is the incidental saturated technique so that a sample of 30 people is obtained. Data were collected by using a questionnaire that had been tested for validity and reliability. The data analysis technique used is multiple regression. The results of this study indicate that work skills, work environment and leadership style have a significant positive effect on employee performance at LG Electronics PT. Head Office in South Jakarta.